Supplementation of creatine and its role in brain function - Leila Abod; Natalia Ilnicka; Daria Matyja; Maria Sadlik; Patrycja Zuziak (Kazimierz Wielki University, 2023)
Introduction and aim. In recent years growing awareness of the society regarding healthy lifestyle leads to increased interest in regular physical activity and usage of dietary supplements. Creatine supplementation is often used among athletes to improve muscle mass, performance and recovery. The aim of this paper is to present the effects of creatine supplementation as well as its function in the body, forms and ways of intake, and potential benefits of its use.   Material and methods. A review of the available literature was performed by searching the PubMed and GoogleScholar databases using the following keywords: creatine, creatine supplementation, sports nutrition, brain function  Analysis of literature. Creatine is one of the most popular supplements recommended for athletes. It catalyzes transfer of phosphate groups into high energy compounds contributing in energy transportation and cellular energy buffering for cells and tissues with high energy demands. Its supplementation improves exercise performance, increases muscle mass and enhances recovery after training. In addition, there are indications that creatine shows promise in reducing symptoms associated with concussion, mild traumatic brain injury, and depression.  Conclusion. Creatine supplementation is used in sport mainly to improve exercise performance and muscle gain,  however, it also plays an important role in brain function. In future it may be used in reducing symptoms associated with concussion, mild traumatic brain injury and depression.